1997
DOI: 10.1007/s004280050098
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of arteriolar and myocardial remodelling in the subendocardial region of patients with hypertensive heart disease and hypertrophic cardiomyopathy

Abstract: Left ventricular hypertrophy is a risk factor for cardiovascular morbidity and mortality. In arterial hypertension and in hypertrophic cardiomyopathy it may be accompanied by clinical signs of myocardial ischaemia resulting from microcirculatory dysfunction in the absence of coronary macroangiopathy. Structural changes of the vascular and interstitial compartment of the heart are involved in the pathogenesis of impaired microcirculation. We investigated patients with hypertensive heart disease (HHD; n = 12) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 52 publications
3
48
0
2
Order By: Relevance
“…As previously found by others, 6,12,30,31 we did observe that all patients studied showed an excessive collagen accumulation into the myocardium. Furthermore, we found that serum PIP correlates directly with myocardial CVF in hypertensives.…”
Section: Pathophysiological Meaningsupporting
confidence: 73%
“…As previously found by others, 6,12,30,31 we did observe that all patients studied showed an excessive collagen accumulation into the myocardium. Furthermore, we found that serum PIP correlates directly with myocardial CVF in hypertensives.…”
Section: Pathophysiological Meaningsupporting
confidence: 73%
“…20 In previous studies, we reported thickening of the media wall and increased periarteriolar fibrosis in hypertensive patients compared with normotensive control subjects. 15 In the present study, we observed a slight, but not significant, reduction in the media cross-sectional area after ACE inhibitor treatment. In addition to the regression of media hypertrophy, angiogenesis with an increase in the number of parallel resistance vessels or a re-remodeling of preexisting material in the vessel wall, causing larger lumen diameter after maximal vasodilatation, can result in an improved coronary reserve.…”
Section: Coronary Blood Flow Measurementssupporting
confidence: 55%
“…Reproducibility of morphometric data has been extensively investigated, and measurements were made according to a previously reported protocol from our group. 5,15,16 …”
Section: Morphological Investigationmentioning
confidence: 99%
“…20 The reduced MBV in patients with HT is considered to indicate structural alterations within the hypertrophied heart. [7][8][9][10]21 Therefore, the determinants of MBV may overlap with the myocardial remodeling seen in the hypertensive heart with increased LVMI.…”
Section: Discussionmentioning
confidence: 99%
“…Important structural remodeling processes that lead to LVH are thickening of the medial wall of the small vessels with reduced lumen diameter and lowered density of coronary capillaries, as well as accumulation of extracellular matrix collagens in the perivascular region. [6][7][8][9][10] Angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) have a regressive effect on the vascular changes in small coronary, renal, and cerebral arteries from animals with HT. 11,12 In patients with HT, a favorable effect of ACEIs and ARBs on the structure of subcutaneous small arteries has been reported.…”
mentioning
confidence: 99%